Steroids and isoquercetin from Lygodium microphyllum - Hadi Kuncoro, Kindi Farabi, Laode Rijai (Journal of Applied Pharmaceutical Science, 2017)
Two steroids, stigma-5(6)-en-3β-ol or β-sitosterol (1) and Stigmast-4-en-3-one (2) and quercetin 3-O-β-D-glucopyranoside or Isoquercetin (3) has been isolated from an extract of n-hexane and ethyl acetate from the leaves of plants Lygodium microphyllum. The chemical structures of compounds 1, 2 and 3 identified based on spectroscopic data and comparison of spectral data obtained from the literature. The discovery of steroid compounds, stigma-5 (6) -en-3β-ol, Stigmast-4-en-3-one, and quercetin 3-O-β-D-glucopyranoside in plants L. microphyllum first reported in this study.
Keywords: Lygodium microphyllum, stigmast-5(6)-en-3&beta; -ol, Stigmast-4-en-3-one,quercetin 3-O-&beta; -D-glucopyranoside, Lygodiaceae.